Using contingent valuation method in estimating the public benefits of the Marikina City Library - Necesario, Roy Santos S.; Dorado, Dan Anothony D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
Public libraries have been constantly finding themselves at a critical standpoint in which they need to prove their economic relevance and worth to their respective contiguous communities. This study employs the contingent valuation method as an economic valuation tool to help justify the continued financial funding of Marikina City Library. The method relies on direct valuation, which involves creating hypothetical scenarios and asking survey respondents to state their 1) willingness and ability to pay (WTP) for a good or service for the hypothetical removal of a service and subsequent offering of it in an open market and 2) willingness to accept (WTA) compensation of invested money in taxation for the removal of the service altogether. The residents of Marikina were divided into users and non-users, defined as those that have not used the library and its programs and services in the past 12 months. Their answers on the survey were also analysed and correlated based on their socio-economic backgrounds of highest educational attainment, income status, and annual family income. In order to remove response bias, the questionnaire handed out were divided into one that informs respondents of the actual tax value they pay for the programs and services of the library, called as the baseline value, and one that does not present such value.
The data gathered were presented with and without value outliers. For library users, with value outliers, informed library users registered a WTP of PHP 77.10 and a WTA of PHP 91.99. These values correlate to a 376% and 449% increase in the value, respectively. Uninformed library users registered a WTP and WTA of PHP 357 and PHP 204 respectively. Without outliers, on the other hand, informed library users gave a WTP and WTA of PHP 59.93 and PHP 53.9, translating to a 292% and 262% increase from the baseline value. Uninformed library non-users gave a WTP and WTA of PHP 203 and PHP 324, respectively. For library non-users, on the other hand, with outliers, informed library non users registered a WTP of PHP 51.68 and WTA of PHP 57.29. These values correlate to a 252% and 279% increase from the baseline values, respectively. Uninformed library non users registered a WTP and WTA of PHP 180.38 and PHP 194, respectively. Without outliers, on the other hand, informed library non-users gave a WTP and WTA of PHP 47.68 and PHP 53.78 respectively, translating to a 233% and 262% increase from the baseline value. Uninformed library non-users gave a WTP and WTA of PHP 163.14 and PHP 152.51, respectively. A general analysis of these data revealed that for both library users and non-users, there is an exponential increase in willingness to support the programs and services of the library. Recommendations as to how better utilize the contingent valuation method are also presented.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Contingent Valuation; Public Libraries -- Finance; Public Libraries -- Use studies; Public Libraries -- Philippines -- Marikina City